2018
DOI: 10.1016/j.jval.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Research and Health Technology Assessment of Rare Disease Technologies: Report of the ISPOR Rare Disease Special Interest Group

Abstract: Identifying and highlighting diverse, but interrelated, key challenges in RD research and HTA is an essential first step toward developing implementable and sustainable solutions. A collaborative multistakeholder effort is required to enable faster and less costly development of safe, efficacious, and appropriate new RD therapies that offer value for money.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 85 publications
0
61
0
5
Order By: Relevance
“…Disease rarity can cause uncertainty in estimates [27] that may reveal to be determinant in health technology assessment [28][29][30], such as utility values. In this study, we aimed to assess the effect of hATTR-PN across HRQoL dimensions, in both carriers and patients, to estimate the impact on utility in comparison to the general population, as well as to explore HRQoL prognostic factors among patients, including disease progression (clinical stage) and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Disease rarity can cause uncertainty in estimates [27] that may reveal to be determinant in health technology assessment [28][29][30], such as utility values. In this study, we aimed to assess the effect of hATTR-PN across HRQoL dimensions, in both carriers and patients, to estimate the impact on utility in comparison to the general population, as well as to explore HRQoL prognostic factors among patients, including disease progression (clinical stage) and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Reimbursement authorities employ different appraisal processes when evaluating new treatment options, especially in the rare disease setting 10 . While some authorities have, as mentioned, questioned added benefit 9 , others have concluded that emicizumab is a therapy that provides significant benefit.…”
Section: Letter To the Editormentioning
confidence: 99%
“…Au niveau européen, les maladies rares sont définies par l'European Medicines Agency (EMA) comme des maladies n'affectant pas plus de 5 personnes sur 10.000 (Rodwell & Aymé, 2015). Ainsi, on est face au paradoxe de la rareté des maladies rares : on dénombre 5.000 à 8.000 maladies rares (European Medicines Agency, 2013), une faible proportion de la population étant atteinte par chacune d'elles; cependant, globalement, les maladies rares touchent un total de 30 millions de patients en Europe (Nestler-Parr et al, 2018). On estime qu'il y a alors 6 à 8 % de la population européenne qui est affectée d'une maladie orpheline, ce qui est équivalent au nombre de patients atteints de diabète en Europe.…”
Section: Numéro 154 • Décembre 2019unclassified
“…Parmi les raisons de cette méconnaissance, on compte le nombre important de maladies rares, leur diversité et leur complexité. De plus, la découverte de nouvelles maladies rares est menée à un rythme soutenu avec cinq nouvelles maladies rares décrites chaque semaine dans la littérature médicale (Nestler-Parr et al, 2018); les médecins doivent alors acquérir une information en perpétuelle évolution.…”
Section: Comment Définir Les Maladies Rares ?unclassified